2012
DOI: 10.3390/molecules17032704
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Anticancer Activity of Rosmarinus officinalis L. Essential Oil Compared to That of Its Main Components

Abstract: Abstract:In this study, Rosmarinus officinalis L. essential oil and three of its main components 1,8-cineole (27.23%), α-pinene (19.43%) and β-pinene (6.71%) were evaluated for their in vitro antibacterial activities and toxicology properties. R. officinalis L. essential oil possessed similar antibacterial activities to α-pinene, and a little bit better than β-pinene, while 1,8-cineole possessed the lowest antibacterial activities. R. officinalis L. essential oil exhibited the strongest cytotoxicity towards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
1
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(160 citation statements)
references
References 19 publications
6
145
1
8
Order By: Relevance
“…Our results are in agreement with previous study (Wang et al 2012), which has reported that α-pinene and β-pinene isolated from Rosmarinus officinalis demonstrated strong cytotoxicity towards human ovarian cancer cell lines (SK-OV-3 and HO-8910) and human hepatocellular liver carcinoma cell line (Bel-7402) in the MTT in vitro assay. Also, Matsuo et al (2011) revealed that α-pinene was able to induce apoptosis evidenced by early disruption of the mitochondrial potential, production of reactive oxygen species, and increase in caspase-3 activity in B16F10 murine melanoma cell.…”
Section: Primary Rat Neuronssupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in agreement with previous study (Wang et al 2012), which has reported that α-pinene and β-pinene isolated from Rosmarinus officinalis demonstrated strong cytotoxicity towards human ovarian cancer cell lines (SK-OV-3 and HO-8910) and human hepatocellular liver carcinoma cell line (Bel-7402) in the MTT in vitro assay. Also, Matsuo et al (2011) revealed that α-pinene was able to induce apoptosis evidenced by early disruption of the mitochondrial potential, production of reactive oxygen species, and increase in caspase-3 activity in B16F10 murine melanoma cell.…”
Section: Primary Rat Neuronssupporting
confidence: 83%
“…α-Pinene was reported to have a broad spectrum of biological activities, i.e. antiinflammatory (Bae et al 2012), antibacterial (Dorman et al 2000) antioxidant (Wang et al 2008), anticancer (Wang et al 2012) and antinociceptive (Him et al 2008) activities.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of C. bejolghota bark oil may be correlated to the diversity of its bioactive compounds. These include 1,8-cineole (comprising 40.24% of the oil) and γ-terpineol (15.41%) in the essential oil, both of which have potent antibacterial and fungicidal activities (Carson et al, 2002;Hendry, Worthington et al, 2009;Wang et al, 2012). Mahboubi and Kazempour, 2009 reported that antibacterial activity of whole essential oil was greater than that obtained from major components alone.…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Kim et al (1995), alguns tem a capacidade de inibir bactérias de origem alimentar e prolongar a vida de prateleira de alimentos processados. Além disso, estudos apontam que essas substâncias possuem efeito antifúngico (Machado et al, 2013), anti--inflamatórios, antinociceptivo e antiespasmódico (Daniel et al, 2009;Adorjan & Buchbauer, 2010;Pinho et al, 2012), atividades antitumoral (Wang et al, 2012;Quassinti et al, 2013) e inseticida (Lima et al, 2014). Portanto, é necessária a implantação de políticas públicas de conscientização, voltadas para o melhor manejo do extrativismo sustentável desse bioma, com vistas à preservação.…”
Section: Fonte: Adaptado De Sebrae (2007)unclassified